PENANAMAN PENDIDIKAN LIFE SKILL DALAM MENINGKATKAN KEMANDIRIAN SANTRI BARU DI PONDOK MODERN GONTOR PUTRA II PONOROGO - Niam, Muhammad Nizhomun (Universitas Muhammadiyah Surakarta, 2018)
The aims of this study are to describe the cultivation of life skill education to improve new students’ independence in Pondok Modern Darussalam Gontor Putra (PMDG) II, Madusari, Siman, Ponorogo Year 2017/2018. The discussion of this study covers the strategy, implementation, also the obstacles and the supporting factors. The type of this study is qualitative research. The subjects of this study are consists of the head master of PMDG, the director of KMI, the teachers, and the students of PMDG Campus II. The object of this study is PMDG Campus II. The data are collected through observation, interviews, and documentation. While the analysis technique is descriptive qualitative. Meanwhile, the validity is determined by triangulation. The results of this study showed that: (1) the cultivation of life skill education to improve new students’ independence in Pondok Modern Darussalam Gontor Putra (PMDG) II are consists of: a. Ensuring the goal; b. set the steps for earning the goal; c. Using some personal approaches; and d. Establish a measuring instrument to measure the success of life skill education to improve new students’ independence. (2) the implementation of life skill education are consists of personal skills aspects b. thinking skill aspects c. social skills aspects d. vocational skills aspects And (3) the obstacles in implementing of life skill education to improve new students’ independence in PMDG Campus II are: the new students’ emotion are still unstable, the supervision of dormitory counselors toward the new students are limited, to get used to PMDG activities are difficult for the new students, the lack of awareness of new students in maintaining the facilities and infrastructure, and the limited capacity of students’ rooms. On the other hand, implementing life skill education to improve new students’ independence in PMDG has supporting factors such as the education integration such as formal, non-formal, and in-formal education platforms, the existence of new students at PM Gontor Putra II is to learn, transform the life skill education, and activity-based are lasting all year. Penelitian ini bertujuan untuk mendiskripsikan penanaman pendidikan life skill dalam meningkatkan kemandirian santri baru di Pondok Modern Darussalam Gontor Putra II, Madusari, Siman, Ponorogo Tahun 2017/2018 yang meliputi strategi penanaman, implementasi, dan faktok pendukung dan penghambatnya. Jenis penelitian ini adalah penelitian kualitatif. Subjek penelitian ini terdiri dari Pengasuh Pondok, Direktur KMI, Asatidz, dan Santri Pondok Modern Darussalam Gontor Putra II. Objek penelitian ini adalah Pondok Modern Darussalam Gontor Putra II, Madusari, Siman, Ponorogo. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Keabsahan ditentukan dengan triangulasi. Teknik analisis data secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa (1) strategi yang digunakan terdiri dari a. Adanya tujuan yang jelas; b. Menetapkan langkah-langkah/cara-cara; c. Menggunakan pendekatan-pendekatan; dan d. Menetapkan tolak ukur untuk menentukan keberhasilan dalam menanamkan pendidikan life skill untuk meningkatkan kemandirian santri baru. (2) implementasi terdiri dari a. aspek personal skill b. aspek tinking skill c. aspek social skill d. aspek vocasional skill (3) Faktor penghambat dan pendukung terdiri dari faktor penghambat meliputi: santri baru masih memiliki tingkat emosional yang masih labil, belum maksimalnya pengawalan terhadap santri baru oleh pembimbing rayon, masih sulitnya santri baru untuk menyesuaikan diri dengan kegiatan-kegiatan Pondok, kurangnya kepedulian santri baru dalam menjaga sarana dan prasarana, dan daya tampung kamar santri terbatas; dan faktor pendukung, meliputi: terintegrasinya tripusat pendidikan, integrasi jalur pendidikan formal, non-formal, dan in-formal, keberadaan santri baru di PM Gontor Putra II adalah menuntut ilmu, transformasi penanaman pendidikan life skill dalam meningkatkan kemandirian santri baru berlangsung sepanjang tahun, dan berbasis kegiatan.